Pergeseran Persepsi Masyarakat Batang Terhadap Madrasah Ibtidaiyah - Nurkhamidi, Aris (Indonesian Journal of Islamic Elementary Education, 2023)
In the midst of the incessant issue of elementary school mergers due to a shortage of students, it turns out that the primary school in Batang Regency is not lacking in students and even continues to increase both in terms of institutions and students.This study aimsto describe and analyze the shift in the perception of the Batang community towards madrasah ibtidaiyah. Data was collected by in-depth interviews, observation and documentation studies. Data validity test was carried out by triangulation of methods and sources. The results of the study show that the perception of the people of Batang towards madrasah ibtidaiyah tends to shift in a positive direction. They are of the view that Madrasah Ibtidaiyah is no longer a second-class school, but is already on par with elementary schools and even has special advantages. This shift in perception occurred because of public awareness about the importance of religious education for elementary school-age children; increasing the quality of madrasah ibtidaiyah; there is equal opportunity for graduates of primary schools to continue their education; and the hope of parents for their children to have morals and practice religious teachings since childhood.